7x+3-(2x-1)=

Simple and best practice solution for 7x+3-(2x-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+3-(2x-1)= equation:


Simplifying
7x + 3 + -1(2x + -1) = 0

Reorder the terms:
7x + 3 + -1(-1 + 2x) = 0
7x + 3 + (-1 * -1 + 2x * -1) = 0
7x + 3 + (1 + -2x) = 0

Reorder the terms:
3 + 1 + 7x + -2x = 0

Combine like terms: 3 + 1 = 4
4 + 7x + -2x = 0

Combine like terms: 7x + -2x = 5x
4 + 5x = 0

Solving
4 + 5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 5x = 0 + -4

Combine like terms: 4 + -4 = 0
0 + 5x = 0 + -4
5x = 0 + -4

Combine like terms: 0 + -4 = -4
5x = -4

Divide each side by '5'.
x = -0.8

Simplifying
x = -0.8

See similar equations:

| 14y-8-10y=0 | | (Y-2)+y=18 | | .6k-.1k=.5k-1 | | x^5-3x^4+4x^3-8x^2+16=0 | | ln(6x-6)=13 | | 4-(x+9)=-x-4-5 | | -4s=-34 | | n-5*2=5 | | 8y^2+36y-72=0 | | 6-(-8)=0 | | 11m+3=8m-18 | | 575=35x-75y | | 2(b-5)=5(b+5)-17 | | 2(y+3)=2y-6(y+5) | | m^2+3=0 | | 5m-3=2(m+3) | | x^2+72=17x | | 35x+50y= | | 162+16m=354 | | 15x^2-10x+15=0 | | 15x^2-10x+15=0 | | 14-7t-16=8t+25-6t | | 4m^2+9=0 | | 4(1h+2)=3(h-2) | | 6x+3-2x=2x+7 | | -12m-3=-12 | | -70-3x+x^2=0 | | 5y+40=-2y-9 | | -0.5m=-9 | | 28n-54=450 | | 12-3=-12 | | 8(4+3a)=32a+5 |

Equations solver categories